Threats to Mental Health Facilitated by Dating Applications Use Among Men Having Sex With Men - Obarska, Katarzyna; Szymczak, Karol; Lewczuk, Karol; Gola, Mateusz (Frontiers in Psychiatry, 2020)
In the last years, dating applications (DAs) have had a significant impact on the way in which people seek sexual and romantic relationships. Social groups, such as men having sex with men (MSM), who can experience discrimination and social isolation, find DAs especially engaging and helpful in finding sexual partners. Previous studies have provided evidence showing vulnerability to mental health problems among the MSM population - these problems can be potentially facilitated by DAs use. Excessive use of DAs is associated with lower well-being and life satisfaction, depression, higher substance use and lower sleep quality. Therefore, there is a need for a better understanding of psychological functioning and risk factors associated with the use of DAs among MSM, which we focus on in this review. We also discuss two relatively new research areas: compulsive sexual behavior disorder and chemsex, and their relation to geosocial-networking mobile technologies. Finally, we point out the limitations of available studies on the mental health of MSM using DAs and propose further research directions.